Covalently bonded boron nitride quantum dot and reduced graphene oxide composite electrode for highly efficient supercapacitors. (1st October 2021) - Lee, Jae Won; Kshetri, Tolendra; Park, Kyoung Ryeol; Kim, Nam Hoon; Park, Ok-Kyung; Lee, Joong Hee
Abstract: This study investigates the synthesis and application of boron nitride quantum dot (BNQD) covalently bonded reduced graphene oxide (rGO) hybrid materials as a novel electrode material for supercapacitors. Because of the p-doping as well as the enhanced hydrophilicity and interfacial bonding force enabled by the hybridization of amine-functionalized boron nitride quantum dot (A-BNQD) with rGO via the chemical coupling reaction, the A-BNQD/rGO shows improved charge carrier density, wettability of electrolyte, and durability. As a result of the synergistic effects, the A-BNQD/rGO as a supercapacitor electrode shows much higher specific capacitance compared to those of rGO and raw BNQD/rGO at a current density of 1 A g −1 . Further, the A-BNQD/rGO shows high cycling stability, maintaining almost 94.38%, even after 10, 000 cycles due to the enhanced interfacial bonding force between the A-BNQD and rGO. Besides, the fabricated symmetric supercapacitor exhibits high specific capacitance (90 F g −1 @1 A g −1 ), an energy density (12.5 Wh kg −1 @0.5 kW kg −1 ), and good cycling stability. This result suggested that the fabricated A-BNQD/rGO has great potential as electrode materials for high-performance supercapacitors.